Evaluating the Impact of Microfinance on Household Welfare: An Empirical Study in Delhi - Dr. Vandana Sethi (International Journal of Engineering and Management Research, 2024)
Microfinance institutions, through the availability of credit to low-income households, create opportunities for self-employment, facilitate the expansion of existing businesses, and positively impact their welfare levels. Many researchers support the view that access to microfinance loans considerably increases household consumption expenditure, while others argue that it has minimal or no impact on average household consumption levels. An attempt has been made in the present paper to study the impact of microfinance on the welfare of households in the context of MFIs in Delhi. The welfare is broadly measured through an increase in households' (HHs) monthly per capita consumption expenditure (MPCE). Using the Logit regression model, an empirical analysis is carried out based on primary data collected from 368 households in Delhi Slums in 2016. The key findings reveal that access to MFI's loans has a positive impact on the MPCE of its clients as an increase in the consumption expenditure after MFI’s loans is larger for HHs in the ‘treatment group’ as compared to those in the ‘control group’.